Sistem Informasi Pariwisata Objek Wisata Tukad Campuhan Tampaksiring Berbasis Web - I Kadek Rizky Sanjaya; Yoga Adiputra; Ramadika Sudewa Putra; Krisna Hermawan (Institut Teknologi Adhi Tama Surabaya, 2021)
This study aims to develop a Web-based Tourism Information System for Tukad Campuhan Tampaksiring Tourism Object as a natural tourism object in the Tampaksiring Tourism Village. The tourism information system aims to make it easier for tourists to get information about Tukad Campuhan Tampaksiring Tourism Object. This research is a type of development research with reference to a place / tourism object that still needs to be developed or a tourist object that is still new. The trial subjects in this study were expert subjects, namely the managers of the Tukad Campuhan tourism object, as well as the tourists as potential users of the information system (users). The results of our research directly to the field show that, in the Tukad Campuhan Tourism Object, development is still very necessary, especially in the Information System. Therefore we have the idea to develop a Web-based Information System, in order to make it easier for tourists to get information about this Tukad mixed tourism object.